When Brooklyn was queer - Ryan, Hugh 1978- (St. Martin's Press, 2019)
"The groundbreaking, never-before-told story of Brooklyn's vibrant and forgotten queer history, from the mid-1850s up to the present day. When Brooklyn Was Queer is a groundbreaking exploration of the LGBT history of Brooklyn, from the early days of Walt Whitman in the 1850s up through the women who worked at the Brooklyn Navy Yard during World War II, and beyond. No other book, movie, or exhibition has ever told this sweeping story. Not only has Brooklyn always lived in the shadow of queer Manhattan neighborhoods like Greenwich Village and Harlem, but there has also been a systematic errasure of its queer hsitory--a great forgetting. Ryan is here to unearth that history for the first time, and show how the formation of Brooklyn is inextricably linked to the stories of the incredible people who created the Brooklyn we know today. Folks like Ella Wesner and Florence Hines, the most famous drag kings of the late-1800s; E. Trondle, a transgender man whose arrest in Brooklyn captured headlines for weeks in 1913; Hamilton Easter Field, whose art commune in Brooklyn Heights nurtured Hart Crane and John Dos Passos; Mabel Hampton, a black lesbian who worked as a dancer at Coney Island in the 1920s; Gustave Beekman, the Brooklyn brothel owner at the center of a WWII gay Nazi spy scandal; and Josiah Marvel, a curator at the Brooklyn Museum who helped create a first-of-its-kind treatment program for gay men arrested for public sex in the 1950s. Through their stories, WBWQ brings Brooklyn's queer past to life"--